Investigating species boundaries using DNA and morphology in the mite Tyrophagus curvipenis (Acari: Acaridae), an emerging invasive pest, with a molecular phylogeny of the genus Tyrophagus - Murillo, Pamela; Klimov, Pavel; Hubert, Jan; OConnor, Barry (Experimental & applied acarology, 2018)
Mites of the genus Tyrophagus (Acari: Acaridae) are among the most widespread and common mites, inhabiting diverse natural and anthropogenic habitats. Some species are pests of agricultural products and stored food and/or live in house dust, causing allergies to humans. We sequenced 1.2 kb of the mitochondrial COI gene for 38 individuals belonging to seven species of Tyrophagus, including T. curvipenis, T. putrescentiae, T. fanetzhangorum, T. longior, T. perniciosus, and T. cf. similis. Molecular phylogenetic analyses (1) recovered two major clades corresponding to the presence or absence of eyespots, and (2) separated all included morphological species. Tyrophagus curvipenis and T. putrescentiae had the lowest between-species genetic distances (range, mean ± SD): 14.20-16.30, 15.17 ± 0.40 (K2P). The highest within-species variation was found in T. putrescentiae 0.00-4.33, 1.78 ± 1.44 (K2P). In this species, we recovered two distinct groups; however, no geographical or ecological dissimilarities were observed between them. Based on our analyses, we document important morphological differences between T. curvipenis and T. putrescentiae. For the first time, we record the occurrence of T. curvipenis in the New World and suggest that it may be an emerging pest as it is currently spreading in agricultural produce.
Keywords: Animal Distribution; fylogeneze; Tyrophagus curvipenis; Sequence Analysis, DNA; COI; Phylogeny; sekvenční analýza DNA; biologická evoluce; respirační komplex IV; rozšíření zvířat; proteiny členovců; mitochondriální proteiny; Tyrophagus phylogeny; Electron Transport Complex IV; Mitochondrial Proteins; Animals; Biological Evolution; zvířata; Acaridae; Genetic distances; DNA barcode; Arthropod Proteins